Optical microsystem for analysis of diffuse reflectance and fluorescence signals applied to early gastrointestinal Cancer Detection - Pimenta, Sara (2015)
The detection of cancer at its earliest stage is crucial in order to increase the probability of a successful treatment. Optical techniques, specifically diffuse reflectance and fluorescence, may considerably improve the ability to detect pre-cancerous lesions. These techniques have high sensitivity to some biomarkers present on the tissues, providing morphological and biochemical information of normal and diseased tissue. The development of a chip sized spectroscopy microsystem, based on these techniques, will greatly improve the early diagnosis of gastrointestinal cancers. The main innovation is the detection of the spectroscopic signals using only few, but representative, spectral bands allowing for miniaturization. This paper presents the mathematical models, its validation and analysis for retrieving data of the measured spectroscopic signals. These models were applied to a set of phantoms clearly representative of gastrointestinal tissues, leading to a more accurate diagnostic by a pathologist. Moreover, it was demonstrated that the models can use the reconstructed spectroscopic signals based only on its extraction on those specific spectral bands. As a result, the viability of the spectroscopy microsystem implementation was proved.